‘Whitestone’—A Specific Polished Stone Tool Raw Material in the Late Neolithic of Southern Hungary - Veronika Szilágyi; Kata Furholt; Zoltán Kovács; Ildikó Harsányi; Anett Osztás; György Szakmány (Heritage)
‘Whitestone’ is a characteristic raw material in the Late Neolithic (Tisza and Lengyel culture) polished stone tool (chisel, adze, macehead) archaeological record in Southern Hungary. However, the lithology—the technical term not reflecting a petrographic definition—needs detailed petrographic-analytical investigations (by optical microscopy, PGAA, and SEM-EDS) to determine the exact rock types and to connect them to specific geological sources. This article identifies the main types of ‘whitestone’ and, furthermore, focuses on the predominant ‘silicified magnesite’ type and the secondary ‘silicified limestone/dolomite’ type. Based on our results, both types originated from the alteration of serpentinized ultramafic assemblages, most probably from the closest magnesitic alteration zones of serpentinite outcrops in Serbia. Thus, the most possible provenance of the Late Neolithic ‘whitestone’ polished stone tools is the Serbian magnesite. These lithologies are in the territory of the Late Neolithic Vinča culture, which was engaged in mass production of ‘whitestone’ tools. This fact indicates the strong relationship of that population with the Tisza and Lengyel communities.